Fooling America how Washington insiders twist the truth and manufacture the conventional wisdom - Parry, Robert (Morrow, 1992)
Fooling America looks at the trivializing of U.S. decision-making and its disastrous impact on the nation. Focusing on how Washington's Conventional Wisdom distorts the public debate, the book explains why the national government and news media have failed to address the country's deepening problems. The crisis, the book argues, rests with a political-social elite that has lost touch with reality. Today's Washington insiders--the image-conscious politicians, the smug TV pundits, the hip journalists and the socially agile cocktail party set--are more interested in who's "in" and who's "out," what's hot and what's not, than in what's happening to the country. This fascination with superficial trends and the endless pronouncements of politically safe insights lie at the heart of the Conventional Wisdom, known as CW to the capital's aficionados